ETIKA PROFESI MEMODERASI PENGARUH INDEPENDENSI, INTEGRITAS, DAN SKEPTISISME TERHADAP KUALITAS AUDIT BPK RI PROVINSI BALI - Wulandari, Putu Dian; Yenni Latrini, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Audit quality is a very complex issue. Audit quality in the public sector is related to the probability of an auditor who can find and report a fraud that occurs in an agency or government. This study aims to examine the effect of independence, integrity, and skepticism on audit quality moderated by professional ethics at the BPK RI Representative Office for Bali Province with a sample of 64 auditors using the purposive sampling method with the Moderated Regression Analysis (MRA) analysis technique. The results of the analysis show that independence, integrity, and skepticism have a positive effect on audit quality. Professional ethics strengthens the influence of independence, integrity and skepticism on audit quality. The theoretical implication of this research is to provide confirmation of agency theory, namely that auditors mediate conflicts that occur between principals and agents as well as attribution theory which explains that audit quality produced by BPK RI auditors Representative for Bali Province can be influenced by the behavior of individual auditors. The practical implication of this research is to provide input to the auditors of the BPK RI Representative Office for Bali Province so that they can carry out audit assignments properly and responsibly.